Effects of avian malaria on male behaviour and female visitation in lekking blue‐crowned manakins. (1st February 2016) - Bosholn, Mariane; Fecchio, Alan; Silveira, Patricia; Braga, Érika M.; Anciães, Marina
Abstract : Avian malaria, the infection by blood parasites of the genus Plasmodium, can reduce host fitness not only through mortality, but also by impairing the expression of sexual selection traits. Although different studies highlight the association of parasitism with a decrease in host reproductive success, few studies have addressed the role of parasites in honest signalling by lekking species. Hence, it is still uncertain which fitness components are affected by parasites in these species. We investigated whether avian malaria is associated with a decrease in mating behaviour of male blue‐crowned manakins Lepidothrix coronata and whether it affects female visitation in leks of a population in the central Amazon. Through behavioural observations, we estimated the rates of total male activity and social interaction, as well as the frequency of female visits at individual perches. We then examined if individuals were infected with Plasmodium spp. using molecular techniques. Avian malaria was associated with a decrease in male mating behaviour in each lek, and mating behaviour correlated with female visitation. Although rates of social interaction were not correlated with avian malaria among males, we observed that interacting with several individuals within a lek may be advantageous for males, as they also vocalized and displayed more, thus increasing their chances of being visited by females. Although female visitation was not associated with avian malaria in individuals or leks, it is still possible that female visitation is indirectly affected by avian malaria through the latter's effects on male activity. We suggest a role for male activity as an honest sexual signal for females. Thus, male display rate could be used by females as cue for the probability of a male being infected.